Prevalence of Stroke in Asian Patients with Sickle Cell Anemia: A Systematic Review and Meta-Analysis. (4th June 2021) - Kuikel, Sandip; Rauniyar, Robin; Kharel, Sanjeev; Bist, Anil; Giri, Subarna; Thapaliya, Sahil; Paudel, Sunanda
Abstract : Sickle cell anemia (SCA) is an inherited autosomal recessive disease. It is caused due to point mutation that substitutes glutamate with valine at the sixth amino acid position of the beta chain of hemoglobin molecules leading to the sickling of the red blood cells and decreased structural deformability. Silent cerebral infarcts are the most common neurological complication of SCA, while overt stroke comprises substantial burden in patients with SCA. This meta-analysis aimed to find the pooled prevalence of overt stroke in SCA patients and discuss the importance of screening them. PubMed, Embase, and Google Scholar were the electronic databases used to search the studies. A total of 765 articles were retrieved upon detailed searching in the abovementioned databases. After a series of removing duplicate articles, title and abstract screening, and full-text review, 20 articles were found eligible and included in the study. The total number of participants from all the included studies was 3, 956, and pooled prevalence of stroke in patients with sickle cell anemia in Asia was found to be 5% (95% CI: 4%, 6%) with a range from 1 to 41%. Stroke occurrence in sickle cell anemia patients is an emergency complication that needs immediate intervention and management. Because of the high prevalence of stroke in patients with sickle cell anemia, clinicians should focus on its prevention and treatment strategies.